Strategi Mengatasi Ketakutan dan Prasangka Terhadap Islamophobia Bagi Umat Beragama - Alya Najmi Putri Arifin; Syahidin Syahidin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to be an effort to overcome fear and prejudice towards Islamophobia among religious communities. Islamophobia can be known as a phobia or fear or prejudice against the Islamic religion. This phenomenon has become a global problem that can threaten peace and harmony in a pluralistic society. Islamophobia is often triggered by a lack of understanding, negative stereotypes, and misleading narratives about Islamic teachings. This research uses a qualitative approach using library source methods and explaining verses from the Koran. The results and discussion of this research show that the Koran refutes Islamophobia. Islamophobia occurs because of a lack of understanding of Islamic teachings. This can be overcome by establishing mutual tolerance between religious communities and providing correct factual data to someone who is considered Islamophobic.